Generation of arbitrary and programmable optical fields - Romero, Mary Jacqueline T.
Optical filed patterns are generated for custom applications such as microfabrication and multi-resolution imaging.Arbitrary optical fields are generated holographically to facilitate parallel-illumination microfabrication.The Gerchberg-Saxton algorithm was used to derive appropriate phase holograms that can be encoded in a spatial light modulator (SLM) to create the tailored optical fields. The uniformity of the intensity distributions is improved by implementation of a modified algorithm wherein the amplitude constraints in the output of Fourier plane is relaxed. Simulation results show that a fidelity value of 96% can be attained with the modified algorithm.Novel point spread functions (PSF) in the form of wavelet-like intensity patterns are generated using analytically derived holograms. A Mexican hat intensity pattern is generated holographically by encoding a π-phase shifting disk to a SLM. The scaling property akin to wavelets can be achieved by changing the ratio of the π-phase shifting disk radius with respect to the radius of aperture truncating the incident Arbitrary optical fields are also generated via phase to intensity conversion afforded by the generalized phase contrast (GPC) method. A modified design of the phase contrast filter consisting of a circular region surrounded by an annular ring is proposed. The performance of the filter is tested by using periodic and aperiodic phase patterns and characterizing the resulting intensity distribution, The modified design suggests a more uniform intensity profile at the output by optimizing the synthetic reference wave (SRW) associated with the filter parameters.